SWOT Analysis of the Transition to Electronic Management of BPHTB System to Prevent Tax Fraud (Case Study at the Regional Revenue Office of Bondowoso Regency) - Cantikasari, Wulan (West Science Journal Economic and Entrepreneurship, 2024)
The Regional Revenue Agency of Bondowoso Regency (Bapenda) is a governmental institution that operates and holds responsibilities in the field of regional revenue. The objective of this research is to analyze the SWOT of transitioning to an electronic BPHTB management system to prevent tax fraud, focusing on Bapenda of Bondowoso Regency. The method used is qualitative descriptive, and data collection is conducted through interview, observation, and documentation techniques. This research gathers data from interviews with employees of Bapenda Bondowoso in the BPHTB field, followed by data management using the SWOT matrix, as well as the IFAS and EFAS matrices. The IFAS research results show a strength score of 1.59 and a weakness factor of 0.68, resulting in an X value of 0.91. The EFAS research results indicate an opportunity factor of 1.8 and a threat factor of 0.8, resulting in a Y value of 1.0. With these results, it is determined that the position is in quadrant 1, as it has positive X and Y values. This signifies that Bapenda of Bondowoso Regency can adopt an aggressive strategy, indicating a strong and potential position for the institution.